Cotton Textile Industry in Kazakhstan: State, Problems and Prospects for the Development - Azhimetova, Gulfari Nurzhanovna (Marketing & Menedzsment, 2019)
Structural restructuring of the Kazakhstan economy through start-up of industrial associations and introduction of cluster technologies is possible mainly in most developed industries including cotton-textile area. Kazakhstan is situated in the centre of broad sales markets of CIS and Eastern European states, which makes it possible to apply the cluster industry development model. Resource endowment of cotton-textile industry of Kazakhstan is determined by such components as natural and climatic conditions favourable for cotton plant cultivation, professional skills of local population, irrigated farm field and manufacturing capacity of cotton processors.